2023
DOI: 10.3390/biomedicines11113036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Surface Roughness of CAD/CAM Metal-Free Materials Used for Complete-Arch Implant-Supported Prostheses: An In Vitro Study

Nataly Mory,
Rocío Cascos,
Alicia Celemín-Viñuela
et al.

Abstract: The roughness of the intra-oral surfaces significantly influences the initial adhesion and the retention of microorganisms. The aim of this study was to analyze the surface texture of four different CAD-CAM materials (two high-performance polymers and two fifth-generation zirconia) used for complete-arch implant-supported prostheses (CAISPs), and to investigate the effect of artificial aging on their roughness. A total of 40 milled prostheses were divided into 4 groups (n = 10) according to their framework mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The surface roughness of prosthetic restorations is of significant importance for bacterial adhesion and colonization of microorganisms. Mory et al investigated the surface texture of high-performance PEEK materials and concluded that it is similar to that of Zirconia and that thermocycling did not cause adverse alterations [54]. Sanchez-Sobrado et al also concluded that the aging conditions of the surrounding environment did not change the properties of PEEK [55].…”
Section: Peekmentioning
confidence: 99%
“…The surface roughness of prosthetic restorations is of significant importance for bacterial adhesion and colonization of microorganisms. Mory et al investigated the surface texture of high-performance PEEK materials and concluded that it is similar to that of Zirconia and that thermocycling did not cause adverse alterations [54]. Sanchez-Sobrado et al also concluded that the aging conditions of the surrounding environment did not change the properties of PEEK [55].…”
Section: Peekmentioning
confidence: 99%